The Alkaloids of Lindera pipericarpa Boerl (Lauraceae) - Lajis, Md Nordin; Mohd Sharif, Atan; Kiew, Ruth; Niyaz Khan, Mohammad; Samadi, Zainuddin (1992)
The alkaloids ofLindera pipericarpa were isolated and characterized as N-methyllaurotetanine, iscocorydine, and nor-isocorydine